The ameliorative potential of Sophora alopecuroides essential oil on CCl4-induced hepatotoxicity in mice; a stereological study - N. Goodarzi*; E. Doorgard; P. Pournaghi (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Sophora alopecuroides, one of the most important herbal medicines is widely grown in west of Iran, and has a long history for treatment of gastrointestinal diseases, leucorrhea, eczema, and psoriasis. The aim of this study was to investigate the ameliorative effect of Sophora alopecuroides essential oil on CCl4-induced hepatotoxicity in mice. Methods: Thirty five male mice were divided into five groups; group I as the negative control, received olive oil intraperitoneally and distilled water orally. Group II as the positive control, received CCl4 mixed with olive oil in the ratio of 5:5, intraperitoneally and distilled water orally. Group III, IV and V received CCl4 and 200, 800 and 1600 µg/kg of S. alopecuroides essential oil through gavages for 45 consecutive days. Results: The results showed that low and intermediate doses of S. alopecuroides essential oil significantly decreased the raised levels of Alanine aminotrasferase and Aspartate aminotransaminase toward control levels (p